Intrinsic risk factors for acute knee injuries among male football players: a prospective cohort study - Engebretsen, A. H.; Myklebust, G.; Holme, I.; Engebretsen, L.; Bahr, R. (Scandinavian Journal of Medicine & Science in Sports, 2011)
This prospective cohort study was conducted to identify the risk factors for acute knee injuries among male football players. A total of 508 players representing 31 amateur teams were tested during the 2004 preseason for potential risk factors for knee injury through a questionnaire on previous injury, Knee Osteoarthritis Outcome Score (KOOS) and a clinical examination. Generalized estimating equations were used in univariate analyses to identify candidate risk factors, and factors with a P-value <0.10 were then examined in a multivariate model. During the football season, 61 acute knee injuries, affecting 57 legs (53 players), were registered. Univariate analyses revealed the KOOS subscores "Pain" and "Function in daily living" (OR for a 10-point difference in score: 1.26, 95% CI 1.03-1.55 and 1.35, 95% CI 0.98-1.85, respectively), any findings at clinical examination (OR: 2.62, 95% CI 1.03-6.68), flexion contraction in range of motion testing (OR: 0.96, 95% CI 0.93-1.00) and varus stress tests in full extension (OR: 8.50, 95% CI 1.85-39.0) and 30° flexion (OR: 5.69, 95% CI 1.73-18.8) as candidate factors. However, in a multivariate analysis, none of these factors were associated with an increased injury risk.